Specific educational strategies using the Anatomage table for physical and occupational therapy students: a questionnaire-based survey - Yoshikawa, Akira; Takagi, Ryo; Enokida, Megumi (Frontiers in Medicine, 2025)
IntroductionAnatomy and physiology are important basic medical sciences and foundational subjects in rehabilitation courses. As an educational tool, the Anatomage table, a virtual dissection table, can help medical and allied health science students to improve their academic motivation and gain a deeper three-dimensional (3D) understanding of human anatomy, to train them as future healthcare professionals. However, specific educational strategies using this tool are unclear. This study therefore aimed to identify specific educational strategies for students enrolled in rehabilitation courses using the Anatomage table, guided by Kolb’s Experiential Learning Cycle (ELC).MethodsThis study involved conducting six neurophysiology lectures, after which the participating physical and occupational therapy students attempted two tasks (report and quiz assignments), specifically designed for this study. After completing the assignments, the students provided the necessary feedback by completing a questionnaire. Qualitative content analysis and correspondence analysis were subsequently conducted.ResultsOur findings revealed that the assignments left a positive impression on many students, enhanced their understating of the human body’s 3D structure, and promoted peer collaboration. The report assignment, which was associated with “Concrete Experience” and “Reflective Observation” in the ELC, was generally perceived as more engaging than the quiz. However, it also revealed that students found both assignments difficult without the required prior knowledge or preparation. The clear instructional videos and stable system performance improved usability, whereas scheduling constraints and limited foundational knowledge were perceived as challenges.DiscussionThese findings suggest that the assignments conducted using this tool support the visual learning preferences typical of early-year rehabilitation students. The sequential use of report and quiz tasks may enhance experiential learning by linking reflection and active experimentation. Integrating such technology-enhanced strategies within a pedagogical framework can suggest complement traditional lectures and cadaver-based anatomy education.